2015
DOI: 10.2989/16085906.2015.1084938
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related disabilities: an extra burden to HIV and AIDS healthcare workers?

Abstract: Healthcare workers need support to respond to the increased needs of people living with HIV who have HIV-related disabilities. Responses need to reflect: 1) increase in rehabilitative staff including in community outreach programmes; 2) skills training in HIV-related disability; and 3) psychosocial support for healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Second, respondents noted that lack of integration creates barriers to provision of holistic care for people living with HIV-related disability. Most notably, HIV services often are not designed to accommodate the needs of people with disabilities, whether HIV-related or otherwise, a finding which has been gaining increasing attention in other research [ 31 34 ]. This situation may be changing as key informants noted, for example, the increasing engagement of DPOs to promote mainstreaming of disability within HIV prevention and care services, though funding gaps for needed resources remain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, respondents noted that lack of integration creates barriers to provision of holistic care for people living with HIV-related disability. Most notably, HIV services often are not designed to accommodate the needs of people with disabilities, whether HIV-related or otherwise, a finding which has been gaining increasing attention in other research [ 31 34 ]. This situation may be changing as key informants noted, for example, the increasing engagement of DPOs to promote mainstreaming of disability within HIV prevention and care services, though funding gaps for needed resources remain.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of knowledge therefore may be seen as a failure of the health system in many respects, rather than the fault of individual patients. A recent study targeting health care workers in the same setting indicated that nursing and other non-therapy staff exclusively used referral systems in cases of disablements in their patients living with HIV [20]. The study also revealed that these health care workers were not aware of what happened with these referrals and what kind of additional intervention or therapy their patients were taking up.…”
Section: Increasing Knowledge Of Health Condition and Medicationmentioning
confidence: 95%
“…The silence surrounding one's HIV status is common amongst PLHIV throughout the world [23] and may be further fuelled in South Africa by the prevailing stigmatisation of PLHIV in their own communities [24][25][26]. The stigma associated with HIV and AIDS is further compounded by the stigma of disability [20,27]. From their interview responses, it would appear that the participants were far more comfortable talking about the symptoms, impairments and activity limitations associated with HIV than they were discussing the disease itself.…”
Section: Tackling Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date it has not been utilized as widely in epidemic and pandemic research. The ICF was chosen to explore the pervasive impact of Human Immunode ciency Virus / Acquired Immune De ciency Syndrome in Africa by van Egeraat et al (15) for its ability to provide a holistic approach. It has also been utilized in a study of people with obesity (16), to describe the impact of functional limitations on quality of life for this population.…”
Section: Functioning Disability and Healthmentioning
confidence: 99%